Intensive and Extensive Speaking: Approaches to Systematizing The Speaking Skills Courses for Undergraduate ELE Students - Chairil Anwar Korompot; Baso Jabu (Jurnal Bahasa dan Sastra, 2019)
Abstract: This article presents a proposal to implement intensive speaking (IS) and extensive speaking (ES) approaches to teaching English speaking courses to student teachers of English in Indonesia. The courses are taught at PBI, an undergraduate English language teacher education program at a university in eastern Indonesia. Speaking courses have been taught at PBI since its first establishment over 58 years ago. However, the lack of effort to make each speaking course a part of speaking course ecology has caused problems such as unclear objectives, competency standards, materials, instructional activities, and assessment. Therefore, systematization of the speaking courses is in order. The authors’ own self-initiated reviews, previous research outcomes, a review of literature indicate that the speaking courses should ideally be systematized using IS and ES. That is, IS is used to teaching the first two beginning speaking courses, and ES to teaching the other two upper-level speaking courses, and/or an additional course on teaching speaking. PBI has never considered adopting such a proposal in its own curricular revision and course development. The adoption and its justification will inform similar institutions both in Indonesia and in the other parts of the world.Keywords: Intensive and extensive approaches, speaking skills, students teachers of EnglishAbstrak: Artikel ini menyajikan usulan bagi penerapan pendekatan intensive speaking (IS) dan extensive speaking (ES) untuk mengajarkan beberapa matakuliah (MK) keterampilan berbicara bahasa Inggris (speaking) bagi mahasiswa calon guru bahasa Inggris di Indonesia. MK-MK tersebut diajarkan di PBI, program studi sarjana pendidikan bahasa Inggris di sebuah universitas di Indonesia bagian timur. MK-MK speaking telah diajarkan di PBI sejak didirikan pertama kali lebih dari 58 tahun yang lalu. Namun, kurangnya upaya untuk membuat setiap MK speaking menjadi bagian dari ekologi MK speaking telah menyebabkan masalah seperti tujuan, standar kompetensi, bahan ajar, kegiatan instruksional, dan penilaian hasil belajar yang tidak jelas. Karena itu perlu ada sistematisasi MK-MK speaking. Hasil tinjauan mandiri, data dari penelitian sebelumnya, and kajian kepustakaan oleh kedua penulis menunjukkan bahwa dua MK speaking tersebut seyogyanya disistematisasi menggunakan IS dan ES. Artinya, IS untuk mengajarkan dua MK speaking pertama, dan ES untuk dua MK speaking yang lain pada tingkat menengah, dan/atau MK keterampilan mengajarkan speaking sebagai tambahan. PBI belum pernah mempertimbangkan usulan seperti ini dalam proses revisi kurikulum dan pengembangan MK. Penerapan dan penjelasan gagasan ini akan menambah perspektif LPTK pendidikan bahasa Inggris baik di Indonesia maupun di belahan dunia yang lain. Kata-kata kunci: Pendekatan intensif and ektensif, keterampilan berbicara, mahasiswa calon guru bahasa Inggris